THE IMPLEMENTATION OF PSAK NO. 45 NON-PROFIT ORGANIZATION ON YAYASAN GEGE MEIMEI INDONESIA (YGMI) - Alfrisca, Cory B1034131004 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
The purpose of this research to know the implementation of PSAK No. 45 non-profit organization in the preparation of financial statements on Yayasan Gege Meimei Indonesia (YGMI) and to know the factors that causing Yayasan Gege Meimei Indonesia (YGMI) do not implemented PSAK No. 45 in their financial statements. This research is qualitative research which is using descriptive method with qualitative approach. The data collection methods of this research are by interview, doing early observation and obtain information about the organization from documents, books or writing data sources.The discussion results of this research show that the staff of Yayasan Gege Meimei Indonesia (YGMI) in prepared financial statements is not a person from accounting sector that understand about non-profit organizationâ€™s financial statements and the educational background is not appropriate with the job positions. Besides that, Yayasan Gege Meimei Indonesia (YGMI) has their own standard for preparing financial statements.Â Keywords: Non-Profit Organization, PSAK No. 45, Financial Statements, Social Organization